Effects of heat treatment, homogenization pressure, and overprocessing on the content of furfural compounds in liquid milk. (27th July 2020) - Xing, Qianqian; Ma, Yanran; Fu, Xiaofei; Cao, Qing; Zhang, Yue; You, Chunping
Abstract: BACKGROUND: Sterilization of milk is aimed at killing the microorganisms present. There are three main sterilization methods commonly used in milk processing: high temperature and short time (HTST) pasteurization, ultrahigh pasteurization (UP), and ultrahigh temperature (UHT) sterilization. The Maillard reaction is of special interest in studying the effect of heat treatment on milk quality. Furfural compounds are one of the typical intermediates of the Maillard reaction, which have safety risks related to mutagenic and genotoxic effects. The furfural compounds content is directly related to the heat treatment intensity. RESULTS: The furfural compounds content was measured using high‐performance liquid chromatography with ultraviolet detection in 12 min. Then, 13 levels of heat treatment intensity (combinations of temperature and time) and three levels of homogenization pressure were selected to study the change of the furfural compounds content after different processing technologies in a pilot plant. The results show a higher temperature treatment can stimulate more Maillard reaction intermediates, such as hydroxymethylfurfural and furfural. A temperature regression evaluation model and content prediction models of hydroxymethylfurfural and furfural were developed to quantify the relationship between the furfural content and heat treatment with the data from the pilot plant. CONCLUSION: Based on the temperature evaluation model, the heating temperature of three milk products was evaluated. The homogenization pressures had little effect on the furfural content in liquid milk. The emergence of the furyl methyl ketone and methylfurfural can be detected after overprocessing of the liquid milk. © 2020 Society of Chemical Industry